1974
DOI: 10.1017/s0022029900014928
|View full text |Cite
|
Sign up to set email alerts
|

Diacetyl, acetoin, 2,3-butyleneglycol, 2-butanone and 2-butanol concentrations in ripening Cheddar cheese

Abstract: Diacetyl, acetoin, 2,3-butyleneglycol, 2-butanone and 2-butanol concentrations have been determined in ripened Cheddar cheese made using Streptococcus diacetilactis DRC1 or Str. cremoris AM 2 or HP as starter culture. Diacetyl content was found to be initially higher in the DRC 1 cheese than in the other 2 cheeses, presumably because this starter readily ferments citrate. The disappearance of acetoin appears to be related to the formation of 2,3-butyleneglycol in DRCl and AM 2 cheeses, but not in HP cheese. On… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
2
1

Year Published

1980
1980
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 14 publications
0
13
2
1
Order By: Relevance
“…Acetoin was detected in some cheeses but, due to response problems in the method of analysis, no statistical evaluation of acetoin was conducted, although the results indicated that high amounts of acetoin and diacetyl were correlated, especially in cheeses with CHCC 4256 (data not shown). The presence of 2,3-butanediol was expected in the cheeses (Keen & Walker, 1974). However, 2,3-butanediol was not detected in control or experimental cheese, in spiked reference cheese slurries or in an aqueous solution, with the D-HS GCMS method used (data not shown).…”
Section: Article In Pressmentioning
confidence: 88%
See 2 more Smart Citations
“…Acetoin was detected in some cheeses but, due to response problems in the method of analysis, no statistical evaluation of acetoin was conducted, although the results indicated that high amounts of acetoin and diacetyl were correlated, especially in cheeses with CHCC 4256 (data not shown). The presence of 2,3-butanediol was expected in the cheeses (Keen & Walker, 1974). However, 2,3-butanediol was not detected in control or experimental cheese, in spiked reference cheese slurries or in an aqueous solution, with the D-HS GCMS method used (data not shown).…”
Section: Article In Pressmentioning
confidence: 88%
“…The same tendency was observed for 2-butanone, although lower amounts of this compound were present (0.6-3.0 mmol kg À1 ). These two compounds may be produced from 2,3-butanediol, by starter LAB (Keen & Walker, 1974) or NSLAB (Speranza et al, 1997), and the results for 2-butanone and 2-butanol indicate that some of these LAB activities had been present, and were especially pronounced in the control cheeses.…”
Section: Article In Pressmentioning
confidence: 93%
See 1 more Smart Citation
“…In their study, diacetyl, which can be produced by the catabolism of citrate or Asp, was found in significantly higher concentrations in cheese produced with CHCC 4256 compared to all other cheeses. Diacetyl may be reduced to acetoin and 2,3-butanediol within the cheese matrix (Keen and Walker 1974). GDH activity has been suggested to be a major criterion for the selection of flavor-producing LAB strains, as the GDH reaction generates α-ketoglutarate necessary for the AT reaction (Tanous and others 2002).…”
Section: Effects Of Probiotic Microorganisms On Sensory Profile Of Prmentioning
confidence: 99%
“…All the volatiles (Table 2) had been reported for Cheddar cheese and, in most cases, were indicated important for Cheddar flavors (Dulley and Grieve, 1974;Keen and Walker, 1974;Wong et al, 1975;Vandeweghe and Reineccius, 1990;Dacremont and Vickers, 1994;Eaton, 1994;Jeon, 1994;Christensen and Reineccius, 1995). VFFA have been shown to provide the necessary aroma background, and possibly contribute to the peppery taste of Cheddar cheese (Eaton, 1994).…”
Section: Resultsmentioning
confidence: 99%